Pelatihan menulis arab menggunakan media kartu bergambar untuk meningkatkan kosakata dan keterampilan menulis siswa MI - Barid Syamsiyah; Farhan Al Jundi (Penamas: Journal of Community Service, 2026)
This community service activity aims to enhance Arabic vocabulary and writing skills at an Islamic Elementary School (Madrasah Ibtidaiyah) in Semarang Regency. A preliminary study identified several challenges, including students’ limited literacy skills, a shortage of Arabic language teachers, and a lack of extracurricular activities to support language proficiency. Furthermore, the school faced constraints regarding vocabulary mastery, instructional media, and time allocation for Arabic lessons, as well as an absence of specialised writing training using pictorial cards. To address these issues, the training used vocabulary games and hijaiyyah letter-writing exercises. The program involved 32 students in grades IV and V, with evaluations conducted through exercises from an Arabic writing instructional module. The results of this community service initiative demonstrated an improvement in students’ vocabulary, evidenced by an increase of at least 10 words related to household objects and 10 names of fruits. Regarding writing skills, students showed neater handwriting and the ability to compose letters into meaningful words. This training demonstrates that pictorial cards are an effective medium for improving students’ vocabulary and writing skills.